Hubungan Tingkat Pengetahuan tentang Diabetes Mellitus dengan Kepatuhan Minum Obat: Relationship Between the Level of Knowledge about Diabetes Mellitus and Adherence to Taking Medication - Novita Kartika Putri; Lensi Natalia Tambunan; Rizki Muji Lestari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Background: Diabetes Mellitus is a group of metabolic diseases characterized by increased blood glucose levels (hyperglycemia). Knowledge results from knowing a person about an object through his senses. Knowledge also includes information that is known and realized by someone. The patient’s non-compliance with DM treatment is currently caused by the patient’s non-compliance regarding treatment for DM patients, which should take a long time according to the severity of DM disease. As a result, DM often causes complications (chronic), especially in the structure and function of blood vessels, and over time, it will cause other complications that are quite fatal. Destination: To find out the relationship between the level of knowledge about Diabetes Mellitus and adherence to taking medication. Method: Using the Literature Review method, supported by Google Scholar in searching for Literature by searching for journals from the last 3 (three) years 2017-2020, and Literature using Indonesian. Result: The are 6 articles snowing that the (P Value) is 0,001, mark 0,001<0,05. So Ho is rejected, and Ha is accepted, which means there is a relationship between knowledge of DM patients and patient compliance with taking medication. Conclusion: From the results of this study, it can be concluded that the level of knowledge of people with Diabetes Mellitus and Compliance with taking medication. This shows that the knowledge of DM patients is generally at a moderate level, which means that the patient’s knowledge is quite good. The patient’s level of medication adherence is low even though the patient knows that taking DM drugs must be routinely and continuously taken so that blood sugar stability does not create complications in other diseases.